SURGICAL TREATMENT OF A GUNSHOT WOUND WITH A FOREIGN BODY: USING THE SENSITIVITY OF THE TACTILE SENSOR - Cherniak, Viktor; Salenko, Oleksandr; Karpenko, Kostyantin; Pryiemska, Viktoriia; Bondar, Leonid; Prokopets, Kostyantin; Gorya, Eduard (SWorld-Ger Conference proceedings, 2025)
Despite the obvious advantages of ultrasound devices, in field conditions, especially during the primary surgical treatment of gunshot wounds in patients affected by shrapnel, the device we offer has undeniable advantages, since it does not require highly